A new checklist of orchid species from Cuba - Mújica, Ernesto; González, Elaine (Lankesteriana: International Journal on Orchidology, 2015)
In 2014, James D. Ackerman and collaborators published the last checklist of Cuban orchid species in the book, “Orchid Flora of the Greater Antilles”. The aim of our study was to determine the current number of orchid species in Cuba and adjacent islands culminating in an updated checklist. We consulted numerous publications and reports, visited four herbaria, and refer to ongoing collaboration with leading specialists. A total of 91 genera and 312 species are documented. We provide comments on taxonomic status on noteworthy species.